Phytoconstituents from Vernonia glaberrima Welw. Ex O. Hoffm. leaves and their cytotoxic activities on a panel of human cancer cell lines - Alhassan, A. M.; Ahmed, Qamar Uddin; Latip, Jalifah; Shah, Syed Adnan Ali; Khan, A'a Y.F.; Sarian, Murni Nazira; Abdul Wahab, Ridhwan; Bakhtiar, M. Taher; Abdullahi, Musa I.; Khatib, Alfi (Elsevier, 2018)
Vernonia glaberrima is a medicinal plant that is used in African traditional medicine for the treatment of skin cancer. The aim of this study was to investigate the anticancer activity of V. glaberrima leaves and isolate its bioactive constituents. Crude methanolic leaves extract of V. glaberrima showing significant cytotoxic activity against cancer cell lines was subjected to chromatographic separation, purification and hydrolysis to yield four compounds namely, nonacosanoic acid, lupeol, 5-methylcoumarin-4-β-glucoside and 4-hydroxy-5-methylcoumarin. Three of the isolated compounds showed significant cytotoxic activity against human malignant melanoma (A375) cell line (IC50: 59.18 ± 2.70 to 139.53 ± 10.79 μg/mL) and human caucasian colon adenocarcinoma (HT-29) cell line (IC50: 4.22 ± 0.13 to 20.0 ± 1.91 μg/mL) while only lupeol displayed significant activity against human breast adenocarcinoma (MCF7) (IC50: 34.15 ± 2.32 μg/mL) cell line. CDK2 receptor and CAIX were identified through molecular docking as potential targets for the bioactive compounds. The findings of this study have revealed the therapeutic potential of V. glaberrima against breast cancer, skin cancer and colorectal carcinoma, respectively and further support its traditional uses in the treatment of skin cancer.